Education and fertility in Egypt: Mediation by women's empowerment - Goleen Samari (Elsevier, 2019)
In 2006, fertility in Egypt reached a two-decade low of 3 births per woman; however, by 2008, the demographic transition reversed, and fertility has remained higher at 3.5 births per woman. Low educational achievement is linked to high fertility. Education is also important in the process of women's empowerment, suggesting that educational achievement lowers fertility through gains in women's agency. However, no studies test this pathway, and evidence on the relationship between education and fertility in Middle Eastern settings is limited. Using longitudinal data from the 2006 and 2012 Egyptian Labor Market Panel Survey (ELMPS), a nationally representative sample of households in Egypt, for 4336 married women aged 15-49 years, this study estimates several linear and mediation regression models of number of births and considers whether women's empowerment explains the relationship between education and number of births. Women's empowerment is operationalized through three measures of instrumental agency: individual household decision making, joint household decision making, and mobility and one measure of intrinsic agency-gender beliefs and attitudes. Higher educational achievement has significant adjusted associations with lower fertility. However, measures of women's agency have mixed mediation associations for education and fertility. Greater individual household decision making and belief in egalitarian gender norms partially mediate the relationship between education and fertility, while greater joint decision making suppresses the relationship. Contrary to expectation, women who have more instrumental agency through more individual and joint household decisions have higher fertility than those who make fewer household decisions. However, women who demonstrate intrinsic agency through greater egalitarian gender beliefs have lower fertility than those who believe in inequitable gender norms. Empowerment programs should focus on improvements in women's education and changing women's intrinsic agency in Egypt, to lower fertility. Keywords: Women's empowerment, Women's education, Agency, Fertility, Mediation, Egypt